Heating-free, room-temperature operation of a radiofrequency-to-light signal transducer with a membrane oscillator and a built-in metasurface mirror. (9th December 2021) - Tominaga, Yusuke; Mikami, Atsushi; Iwamura, Akiya; Usami, Koji; Takeda, Kazuyuki
Abstract: We present an electro-mechano-optical radiofrequency (rf)-to-light signal transducer robust against laser heating and thus operational at room temperature. A metal-free, low-loss metasurface mirror and an aluminum electrode made separately on a Si3 N4 membrane oscillator comprise a chain of electro-mechanical and opto-mechanical systems, mediating electrical and optical signals through the (2, 2)-mode characteristic oscillation. We demonstrate up-conversion of rf signals at 175.2 MHz by 6 orders of magnitude in frequency to an optical regime with the transfer efficiency of 2.3 × 10 −9, also showing stable operation due to reduced laser heating of the mirror.